2016
DOI: 10.1002/2015jd024550
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric drivers of Greenland surface melt revealed by self‐organizing maps

Abstract: Key Points:Surface melt anomalies correspond with anomalies in energy advection and the local energy balance.Atmospheric patterns that enhance surface melt have increased in frequency in the last 36 years.Accelerating Greenland melt partially due to synoptic changes, but mostly to Arctic warming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 78 publications
7
69
0
Order By: Relevance
“…This study joins an existing body of research describing the synoptic atmospheric conditions associated with GrIS surface mass loss. Previous studies have detailed the roles of blocking high‐pressure systems (Hanna, Jones, et al, ; Hanna et al, ; McLeod & Mote, ; Mioduszewski et al, ) and warm air advection by extratropical cyclones (McLeod & Mote, ; Mote, ; Schuenemann & Cassano, ) in forcing ice sheet melt. We propose that moisture transport by ARs is a complementary and interrelated mechanism affecting GrIS SMB rather than a distinct phenomenon.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study joins an existing body of research describing the synoptic atmospheric conditions associated with GrIS surface mass loss. Previous studies have detailed the roles of blocking high‐pressure systems (Hanna, Jones, et al, ; Hanna et al, ; McLeod & Mote, ; Mioduszewski et al, ) and warm air advection by extratropical cyclones (McLeod & Mote, ; Mote, ; Schuenemann & Cassano, ) in forcing ice sheet melt. We propose that moisture transport by ARs is a complementary and interrelated mechanism affecting GrIS SMB rather than a distinct phenomenon.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The SOM classification method has become increasingly common in the atmospheric sciences due to its usefulness in linking patterns of large‐scale atmospheric variability to their finer‐scale local and regional effects (Harman & Winkler, ; Hewitson & Crane, ). Several recent studies (e.g., Cassano et al, ; Mioduszewski et al, ; Schuenemann et al, ; Schuenemann & Cassano, , ; Skific et al, ) have used SOMs to analyze the impacts of synoptic atmospheric variability across the Arctic and Greenland. While most of these studies characterized the synoptic circulation by applying SOM classifications to atmospheric pressure or geopotential height, a few recent studies (Radić et al, ; Swales et al, ; M16) have shown that SOMs can also be used to directly categorize IVT patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Fettweis et al [32] used a circulation type classification to show that since 2003, phases with a negative North Atlantic Oscillation (NAO) index occurred more frequently in summer, leading to increased northward transport of warm air to west Greenland, explaining an estimated 70% of the recent summer warming. Mioduszewski et al [70] developed a summer Arctic synoptic climatology by applying self-organizing maps to daily 500-hPa geopotential height fields of the Modern Era Retrospective Analysis for Research and Applications reanalysis (MERRA, 1979-2014). The study confirms that the largest positive GrIS melt anomalies occur in concert with strong northward transport of heat and moisture.…”
Section: Large-scale Atmospheric Circulationmentioning
confidence: 99%
“…Analysis of mid-tropospheric summer (JJA) sea level pressure (SLP) reveal statistically significant increases over Greenland and north of the Canadian Arctic Archipelago coupled with significant negative trends over northern Eurasia and Canada from 1979 to 2014 (Serreze et al, 2016;Bezeau et al, 2015), dominated by a clear shift in the last decade (2005 to 2014) towards large positive SLP anomalies over the central Arctic Ocean and Greenland. This pattern favors both summer sea ice loss (e.g., Wang et al, 2009;Ogi and Wallace, 2007) and Greenland surface melt (Hanna et al, 2013;Mioduszewski et al, 2016;Ballinger et al, 2017). Additionally, advection of warm and humid air masses appears to be the primary factor initiating sea ice melt onset (MO) (Boisvert and Stroeve, 2015;Mortin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%